2018
DOI: 10.5539/ies.v11n5p123
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Body Image Satisfaction and Bulimia Nervosa among King Saud University Students

Abstract: The study aimed at examining the relationship between body image satisfaction and bulimia nervosa among the students of education faculty at king said university students. The author used the tests of bulimia nervosa and body image test. The researcher verified tests reliability. Students from King Saud University randomly selected (No. 337) participated in the study. Overall mean of the body image satisfaction test scored 3.66 degrees, and the overall mean of the bulimia nervosa test scored 3.42 degrees. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Kendzor et al (2009); Hales et al (2017); Solmi et al (2016)agree that many women suffering from BNtrust that smoking reduces appetite and could be a convenient way of controlling appetite and weight. Fatima, Fatima, & Anwar (2018) like (Aljomaa, (2018) established that students with low and high BMI (body mass index) were at a higher risk of disordered eating than those with BMI scores.The study concluded that body image disturbance was the most robust factor in eating disordered behavior, including BN. A similar study was carried out by Allihaibi (2015), who also reported that in Makkah Al-Mukarramah, Saudi Arabia, the underweight student had the highest eating disorders at 29%.…”
Section: Literature Review:-mentioning
confidence: 99%
“…Kendzor et al (2009); Hales et al (2017); Solmi et al (2016)agree that many women suffering from BNtrust that smoking reduces appetite and could be a convenient way of controlling appetite and weight. Fatima, Fatima, & Anwar (2018) like (Aljomaa, (2018) established that students with low and high BMI (body mass index) were at a higher risk of disordered eating than those with BMI scores.The study concluded that body image disturbance was the most robust factor in eating disordered behavior, including BN. A similar study was carried out by Allihaibi (2015), who also reported that in Makkah Al-Mukarramah, Saudi Arabia, the underweight student had the highest eating disorders at 29%.…”
Section: Literature Review:-mentioning
confidence: 99%
“…Research on EDs in the Kingdom of Saudi Arabia (KSA) has been conducted in local settings (Alhazmi & Al Johani, 2019; Aljomaa, 2018; AlShebali et al, 2021; Alsulaiman & El Keshky, 2019; Alwosaifer et al, 2018; Anitha et al, 2019; Fatima et al, 2018; Hussein et al, 2016; Taha et al, 2018), mostly focusing on university students, and using screening instruments such as Eating Attitude Test‐26 (EAT‐26; Garner et al, 1982), and the Eating Disorder Diagnostic Scale−DSM‐5 (EDDS; Stice et al, 2000). There is a need for research studies aimed at determining the prevalence of EDs in representative population samples, using standardized assessments.…”
Section: Introductionmentioning
confidence: 99%